Dietary Treatment for NAFLD: New Clinical and Epidemiological Evidence and Updated Recommendations - Zelber-Sagi, Shira (Seminars in Liver Disease, 2021)
The key factor in preventing and treating nonalcoholic fatty liver disease (NAFLD) is a holistic lifestyle modification approach, encompassing diet based on healthy eating patterns of unprocessed foods, exercise, balanced drinking, and smoking habits. The Mediterranean diet and other healthy dietary patterns can reduce liver fat and may be related with lower disease progression. The type of diet should be tailored to the patient's cultural and personal preferences. Changing dietary composition without reducing caloric intake may offer an additional and sometimes more feasible alternative, so that the nutritional treatment incorporates, but is not focused on, weight reduction goals. The growing global consumption of ultra-processed foods, which is the polar opposite of the Mediterranean diet and its concept of home-based cooking, poses a great challenge in the prevention of NAFLD and probably hepatocellular carcinoma.This review will cover the most updated clinical and epidemiological evidence for lifestyle treatment in NAFLD and provide practical treatment tools.
Keywords: dietary composition; fructose; ultra-processed food; processed meat